Characterization of Rice Husk Silica Foam Fabricated by Slurry Method for Water Filter Application - Othman, Nurul Ain Shuhada; Ahmad, Sufizar (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Rice husk, a byproduct of rice milling composed of cellulose, hemicellulose, lignin, silica and ash. This study investigates the characteristic of silica from rice husk  processed via the slurry method for water filter application. The aim from this research are producing a silica using rice husk with slurry method, analyse the physical properties and examine the surface structure of silica after sintering process and compare the properties between rice husk from Pasir Tumboh and Pasir Puteh. The rice husk is gathered, cleaned, and combined with other ingredients to form a slurry, which is then applied to a substrate. The properties of silica such as density and porosity, are influenced by the composition of material in slurry. This research focuses on the production of silica for water filter application by using a combination of silica, distilled water and Polyvenyl Alcohol (PVA) as a binder agent, with the composition of silica set at 45 wt.%, 50 wt.% and 55 wt.%. The filters are evaluated through physical test including density and porosity. Surface morphology is analysed using Scanning Electron Microscopy (SEM). The results states that 45 wt.% silica from Pasir Tumboh produce a sample with a porosity of 76.58% and density of 0.52 g/cm3. While Pasir Puteh created a sample with porosity of 86.40% and density of 0.30 g/cm3. Hence, it is shows that silica from Pasir Puteh produce the best result for water filter application as a higher porosity water filter could improve water flow rate and reduce the clogging while lowest density would  increase the surface area and effective in water filtration.